Important Biological Issues for Elementary Pupils – A Study of Elementary Pre-service Teachers’ Conceptions - Eija Yli-Panula; Eila Jeronen; Heidi Seiko-Ahlstrom; Elsa Ruotsalainen (The Norwegian Centre for Science Education, University of Oslo, 2022)
Previous studies show teachers’ conceptions about subject matter influencing their teaching decisions. In the survey, it has been investigated what kind of conceptions elementary pre-service teachers have concerning the issues they find important in teaching and management of biology in order to provide adequate learning for Finnish elementary school pupils. Totally 267 participants answered the questionnaire. The data was analysed by inductive content analysis. Biological content knowledge (60 %), skills (15 %), and experience (11 %) formed the greatest part of the mentioned important issues (totally 936). Other ones (e.g. attitudes, teaching) comprised less than 10 %. The issues of knowledge were mentioned significantly more often than the other ones. The results show that the participants had hardly any view of the totality concerning elementary biology education. So, teacher educators should discuss and implement new strategies to make biology education more comprehensive for elementary pre-service teachers.